CLINICAL EVALUATION OF LEECHING AND SURGICAL EXCISION IN THE MANAGEMENT OF EXTERNAL THROMBOSED HAEMORRHOIDS - Kulkarni, N.H.; Patil, Sachin N. (International Journal of Ayurveda and Pharma Research, 2015)
Hemorrhoids is a disease, which is very specific to human race only, due to its erect posture. According to Ayurveda the disease comes under the heading of Maharogas because it has four major qualities attributed to Maharogas, which are Maramshraya Dirghakalanubandhi, Dushchikitsya and Tridosha involvement. Since the dawn of civilization, this notorious and problematic disease is not uncommon. If not treated properly or neglected it may lead to so many complications like thrombosis, strangulation, gangrene etc. Similarly for the treatment of piles, there are number of measures starting form injection therapy to the latest cryosurgery and laser therapy. Acharya Sushruta had advocated to carryout Raktamokshana in Shushkarsha. Amongst the different methods of Raktamokshana, Jalaukavacharana being a simple procedure. This procedure is painless and can be carried out easily. In the present study an effort has been made to compare an old para surgical modality with the existing modern surgical modality in the management of external thrombosed haemorrhoids.